Pengaruh Metode Outdoor Learning Terhadap Hasil Belajar Ipa - Putri Febiyani Tri Amalia Fathul Hidayah (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of the outdoor learning method on science learningoutcomes for 4th grade students of SD Negeri Rejowinangun 6 Uatra. This study uses acomparison method of pre-test and post-test results. Subjects in this study were takenrandomly. The sample in this study found 12 students. The results showed that there wasa positive influence from the use of outdoor learning methods on science learning outcomesfor Grade 4. This was evidenced by the average pre-test result of 61.47 and the post-testscore of 92.00.